Adaptive control-theoretic detection of integrity attacks against cyber-physical industrial systems - Jose Rubio-Hernan; Luca De Cicco; Joaquin Garcia-Alfaro (Trans. Emerg. Telecommun. Technol., 2018)
The use of control-theoretic solutions to detect attacks against cyber-physical industrial systems is a growing area of research. Traditional literature proposes the use of control strategies to retain, eg, satisfactory close-loop performance, as well as safety properties, when a communication network connects the distributed components of a physical system (eg, sensors, actuators, and controllers). However, the adaptation of these strategies to handle security incidents is an ongoing challenge. In this paper, we survey the advantages of a watermark-based detector against some integrity attacks as well as the weaknesses against other attacks. To cover these weaknesses, we propose a new control and security strategy that complements the watermark-based detector. We validate the detection efficiency of the new strategy via numeric simulation. Experimental results are also presented by using a laboratory testbed based on supervisory control and data acquisition industrial protocols. image image In this paper, we survey the advantages of a watermark-based detector against some integrity attacks as well as the weaknesses against other attacks. To cover these weaknesses, we propose a new control and security strategy that complements the watermark-based detector. We validate the detection efficiency of the new strategy via numeric simulation. Experimental results are also presented by using a laboratory testbed based on supervisory control and data acquisition industrial protocols.